Global Fractional Anisotropy: Effect on Resting-state Neural Activity and Brain Networking in Healthy Participants. (15th September 2021) - Porcu, Michele; Cocco, Luigi; Puig, Josep; Mannelli, Lorenzo; Yang, Qi; Suri, Jasjit S.; Defazio, Giovanni; Saba, Luca
Graphical abstract: Highlights: The global fractional anisotropy (gFA) is a marker of white matter integrity. gFA is negatively correlated with age. gFA influences neural activity and connectivity at various levels. Abstract: The global fractional anisotropy (gFA) is a structural marker of white matter myelination and integrity. Previous studies already evidenced that aging-related reduced integrity of specific white matter tracts is associated with decreased functional connectivity in several hubs. However, the correlations between gFA and functional brain connectivity remain unknown. In this cross-sectional study, we analyzed structural and functional MR datasets of 79 healthy participants from the Leipzig Study for Mind–Body–Emotion Interactions. DTI model-based method was used to quantify gFA values. We tested associations between gFA, age, and gender. The fractional amplitude of low-frequency fluctuations (fALFF) and ROI-to-ROI connectivity were analyzed in a regression model for evaluating the effects of gFA on brain activity and networking, respectively. A negative correlation was found between gFA and age ( ρ  = −0.343; p  = 0.002). No statistically significant correlation as found between gFA and gender ( p  = 0.229). Higher values of gFA were associated with increased brain regional activity, including areas of the default mode network. There was a higher degree of correlation between some regions, particularly those that conform to the limbic system. Our study demonstrates that gFA influences regional neural activity and brain networking on resting, particularly the limbic system.